Marginal sinks or potential refuges? Costs and benefits for coral-obligate reef fishes at deep range margins. Issue 1890 (7th November 2018) - MacDonald, Chancey; Jones, Geoffrey P.; Bridge, Tom
Abstract : Escalating climate-related disturbances and asymmetric habitat losses will increasingly result in species living in more marginal habitats. Marginal habitats may represent important refuges if individuals can acquire adequate resources to survive and reproduce. However, resources at range margins are often distributed more sparsely; therefore, increased effort to acquire resources can result in suboptimal performance and lead to marginal populations becoming non-self-sustaining sink-populations. Shifting resource availability is likely to be particularly problematic for dietary specialists. Here, we use extensive in situ behavioural observations and physiological condition measurements to examine the costs and benefits of resource-acquisition along a depth gradient in two obligate corallivore reef fishes with contrasting levels of dietary specialization. As expected, the space used to secure coral resources increased towards the lower depth margin. However, increased territory sizes resulted in equal or greater availability of resources within deeper territories. In addition, we observed decreased competition and no differences in foraging distance, pairing behaviour, body condition or fecundity at greater depths. Contrary to expectation, our results demonstrate that coral-obligate fishes can select high-quality coral patches on the deeper-reef to access equal or greater resources than their shallow-water counterparts, with no extra costs. This suggests depth offers a viable potential refuge for some at-risk coral-specialist fishes.